Appropriate Concentration of Curcumin as a Growth Factor in Neural Stem Cells - Novianti, Titta; Kurniawan, Muhamad Panji Januarsyah; Nainggolan, Ita M (Al-Hayat: Journal of Biology and Applied Biology, 2024)
The growth of Neural Stem Cell (NSC) in adult organisms is limited. Therefore, growth factors are needed to stimulate NSC cell proliferation and differentiation. Herbal Curcumin may be a growth factor. We promoted the growth of Cryopreserved Rat Cortical NSC cells with Curcumin (0.1 µM; 0.5 µM; 1 µM; 2 µM), DMSO, and synthetic growth factors (bFGF, TGF, and heparin). We analyzed the proliferation ability of NSCs by WST-1 assay, cell morphology, and expression of NCS cell marker genes (Nestin, MAP, and Sox2). Morphological analysis showed that cells reproduced optimally at 0.5 µM. The one-way ANOVA and Tukey's posthoc test on the WST-1 test showed significant differences between 0.5 µMCurcumin and other treatment groups. Sox2, MAP-2, and Nestin gene expression peaked at 0.5 µM. The appropriate concentration of Curcumin to stimulate NSC proliferation is 0.5 µM. Herbal extract curcumin has the same effect as commercial growth factors and can substitute synthetic growth factors. Curcumin acts as a growth factor that stimulates the proliferation of mouse NSCs.